Phage-Based Artificial Niche: The Recent Progress and Future Opportunities in Stem Cell Therapy. (3rd April 2019) - Shrestha, Kshitiz Raj; Yoo, So Young
Abstract : Self-renewal and differentiation of stem cells can be the best option for treating intractable diseases in regenerative medicine, and they occur when these cells reside in a special microenvironment, called the "stem cell niche." Thus, the niche is crucial for the effective performance of the stem cells in both in vivo and in vitro since the niche provides its functional cues by interacting with stem cells chemically, physically, or topologically. This review provides a perspective on the different types of artificial niches including engineered phage and how they could be used to recapitulate or manipulate stem cell niches. Phage-based artificial niche engineering as a promising therapeutic strategy for repair and regeneration of tissues is also discussed.